2015
DOI: 10.1007/s11199-015-0469-x
|View full text |Cite
|
Sign up to set email alerts
|

Reactions Toward Men Who Have Taken Parental Leave: Does the Length of Parental Leave Matter?

Abstract: There is some evidence from research in the US that the work-related characteristics of men who take parental leave may be evaluated negatively. In 2007, Germany introduced a new law that encourages men to take parental leave by granting 2 extra months for the second parent to stay home. Since the introduction of this law, the proportion of fathers taking parental leave has increased substantially, but the majority of men take only the minimum of 2 months. We investigated how taking a parental leave affected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Both managers and employees, but more managers, reported the inconvenience of leave use to the organization, the administrative struggle (e.g., replace and train a leave replacement, required paperwork), loss of productivity, and the increased workload that results when the organization chooses not to backfill a position while an employee is on leave. Fleischmann and Sieverding (2015) found that in Germany, longer leaves were not associated with increased peer backlash, but in this organization failure to backfill those on leave, especially when leaves are 35 weeks long, appears to increase frustration, as it has a direct and problematic increase on coworkers’ workload. This frustration is compounded when absences mean more shifts and exposure to physical threat.…”
Section: Discussionmentioning
confidence: 75%
“…Both managers and employees, but more managers, reported the inconvenience of leave use to the organization, the administrative struggle (e.g., replace and train a leave replacement, required paperwork), loss of productivity, and the increased workload that results when the organization chooses not to backfill a position while an employee is on leave. Fleischmann and Sieverding (2015) found that in Germany, longer leaves were not associated with increased peer backlash, but in this organization failure to backfill those on leave, especially when leaves are 35 weeks long, appears to increase frustration, as it has a direct and problematic increase on coworkers’ workload. This frustration is compounded when absences mean more shifts and exposure to physical threat.…”
Section: Discussionmentioning
confidence: 75%
“…The existing body of literature and research on fathering and flexible work shares conceptual and theoretical insights, and methodological frames of reference, although there are notable points of difference that invariably result from the paradigmatic conventions of each discipline. For example, research from psychology has primarily focused on how gender norms (McLaughlin & Muldoon, 2014;Vandello et al, 2013), workplace culture, and organizational expectations have an impact on fathers' experiences of work-family conflict (Allard et al, 2011;Cooklin et al, 2015;Huffman, Olson, O'Gara, & King, 2014), and it has examined the dominant perceptions and attitudes surrounding fathers who use workplace flexibility (Coleman & Franiuk, 2011;Fleischmann & Sieverding, 2015;Rudman & Mescher, 2013). In this literature, there is often a singular focus on the individual, by which the individual's actions and perceptions are explored in the context of rules, expectations, norms, and identities.…”
Section: Disciplinary Approaches To Examiningmentioning
confidence: 99%
“…In practice, the length of the financial support for parental leave can increase from 12 to 14 months provided that fathers use the parental benefit for at least 2 months. Recent research aiming at investigating whether German men who take parental leave are judged negatively in the workplace revealed that, in contrast with women who experience penalty for motherhood [ 40 ], fathers do not face backlash effect when they take a long parental leave [ 88 ]. The authors concluded that "gender role attitudes have changed".…”
Section: Discussionmentioning
confidence: 99%
“…Tempering this view, the present study indicates that even in countries promoting incentives for fathers to take parental leave, motherhood myths—and specifically the belief that mother's work threatens the family—are still a justification for gender discrimination in the workplace. With regard to practices, it should be noted that shared parental leave policies, whose purpose is to foster gender equality in the labor market, often fail to meet this objective, with the majority of fathers actually taking the minimum length of leave entitlement, or no parental leave at all, and the majority of mothers still facing the majority of childcare [ 88 ]. Once again, more research is needed to document the process of mutual influences between changing family policies and the maintenance of the gender status quo via justifying beliefs.…”
Section: Discussionmentioning
confidence: 99%